2017
DOI: 10.21276/ijrdpl.2278-0238.2017.6(2).2571-2575
|View full text |Cite
|
Sign up to set email alerts
|

Development and in-vitro evaluation of Furosemide Solid Dispersion using different Water Soluble Carriers

Abstract: Abstract:Objective: The objective of the present investigation was to improve solubility and dissolution characteristics of Furosemide, which might offer improved bioavailability. The bioavailability of the drug when taken orally is limited by the relatively low solubility. Furosemide is a loop diuretic (a 'water pill') used to treat congestive heart failure, oedema and sometimes hypertension. Method: The solid dispersion of Furosemide was prepared by Solvent evaporation method by using 1:1, 1:2 and 1:3 ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Our findings in this study are in agreement with the study results of Meenakshi and Khan; they found that solid dispersions of FUR with PVP-K30 prepared by solvent evaporation method in 1:4 drug: carrier ratio enhanced the solubility to a greater extent compared with pure FUR [25]. Soni et al evaluated the aqueous solubility of FUR solid dispersions prepared by the solvent evaporation method with PEG and PVP-K30, solid dispersions with PVP-K30 in 1:2 ratio showed a 4.5-fold increase in aqueous solubility of FUR compared with pure FUR [12]. Solubility study of FUR solid dispersions with PEG and PVP-K30 prepared by fusion and solvent evaporation method indicated that increasing the concentration of the carrier will enhance the aqueous solubility of the poorly soluble drug; this finding is reported by Patel et al, they found that the solubility of FUR-PVP K30 solid dispersions in a ratio of 1:10 was enhanced by 23-fold compared with poorly soluble FUR [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings in this study are in agreement with the study results of Meenakshi and Khan; they found that solid dispersions of FUR with PVP-K30 prepared by solvent evaporation method in 1:4 drug: carrier ratio enhanced the solubility to a greater extent compared with pure FUR [25]. Soni et al evaluated the aqueous solubility of FUR solid dispersions prepared by the solvent evaporation method with PEG and PVP-K30, solid dispersions with PVP-K30 in 1:2 ratio showed a 4.5-fold increase in aqueous solubility of FUR compared with pure FUR [12]. Solubility study of FUR solid dispersions with PEG and PVP-K30 prepared by fusion and solvent evaporation method indicated that increasing the concentration of the carrier will enhance the aqueous solubility of the poorly soluble drug; this finding is reported by Patel et al, they found that the solubility of FUR-PVP K30 solid dispersions in a ratio of 1:10 was enhanced by 23-fold compared with poorly soluble FUR [21].…”
Section: Discussionmentioning
confidence: 99%
“…The solid dispersions formed were further dried in an oven (Nuve, Turkey) at 40° for 24 h. All the resulting solid dispersions were scraped, pulverized in a mortar and sieved through a 60-mesh sieve. Following that, all solid dispersions were stored in amber glass bottles and kept in the desiccator until further use [12].…”
Section: Solvent Evaporation Methodsmentioning
confidence: 99%
“…The other factor that plays a major role in solubility enhancement is the nanosize, porous, and amorphous structure of GP in GPNs formulations; that give a large surface area available for dissolution in addition to the high internal energy of the amorphous state compared to the crystalline state that led to a faster dissolution rate. The reverse relationship between the dissolution rate and the particle size was verified by many studies, which deliberated the relation between the particle size and the solubility of poorly soluble drugs (Soni et al., 2017 ; Cai et al., 2018 ). At the same time, the greater wettability increased the dissolution rate of the SFCL nanosized powder (Chaudhari et al., 2012 ).…”
Section: Resultsmentioning
confidence: 95%
“…Then after suitable dilution the solution was assayed for drug content using UV spectrophotometer by determining the absorbance at 363nm using 0.1N NaOH as blank (21) . The percentage of drug content in the SD was measured by using the following equation (22) . rug content (%) = Actual amount of drug in solid dispersions Theoretical amount of drug in solid dispersions × 100…”
Section: Determination Of Drug Content Of the Prepared Sd Of MLXmentioning
confidence: 99%